MENTAL HEALTH IMPACTS OF CLIMATE CHANGE: AN EMERGING PUBLIC HEALTH CONCERN - Ita Soegiarto (Cognitionis Civitatis et Politicae, 2025)
Climate change has increasingly been recognized as not only an environmental crisis but also a significant public health concern, particularly in terms of its impact on mental health. Extreme weather events, rising temperatures, and environmental degradation can lead to psychological stress, anxiety, and a sense of helplessness in affected populations. These mental health impacts are particularly pronounced in vulnerable communities with limited resources to adapt to changing environmental conditions. This study aims to explore the mental health consequences of climate change, focusing on how individuals and communities experience and respond to climate-related stressors. Using a mixed-methods approach, this research combines quantitative surveys and qualitative interviews to gather data from populations in areas highly affected by climate change. The study examines both the direct psychological impacts of climate events, such as post-traumatic stress disorder (PTSD), as well as the more subtle, chronic effects like eco-anxiety and feelings of loss. The findings indicate that climate change has a profound and multifaceted impact on mental health. Results show a significant increase in reported cases of anxiety, depression, and stress among those living in climate-vulnerable regions. Additionally, communities that have experienced extreme weather events, such as hurricanes or wildfires, report higher levels of trauma-related mental health issues. In conclusion, this research underscores the urgent need for mental health interventions as part of climate adaptation strategies. Addressing the mental health dimension of climate change is crucial for building resilient communities that can better cope with both the immediate and long-term effects of environmental disruption.